Vestibular Rehabilitation as an Early Intervention in Athletes Who are Post-concussion: A Systematic Review - Gabrielle Babula; Edward Warunek; Katherine Cure; Grace Nikolski; Heather Fritz; Susan Barker (North American Sports Medicine Institute, 2023)
# Background Sports-related concussions (SRC) are a common injury sustained by many athletes of all different age groups and sports. The current standard treatment is rest followed by aerobic activity. Minimal research has been done on the effects of vestibular rehabilitation for concussion treatment, especially in physical therapy practice. # Objective The purpose of this study was to examine the effects of early intervention of vestibular rehabilitation (VRT) on an athlete's time to return to play compared to rest alone. # Study Design Systematic Review # Methods Two searches were conducted (August 2021 and January 2022) using databases: CINAHL complete, MEDLINE, PubMed, and Wiley online database. One hand search was performed to find relevant articles. Search terms included "vestibular rehabilitation" or "vestibular therapy" and "concussion" or "mild traumatic brain injury" or "mTBI" and "athletes" or "sports" or "athletics" or "performance", and "early interventions" or "therapy" or "treatment". Inclusion criteria were athletes with a SRC, incorporation of vestibular rehabilitation in athletes' recovery, and early vestibular intervention tools. Tools used to assess quality and risk of bias were the PEDro scale and the _Oxford Centre for Evidence-Based Medicine 2011 Levels of Evidence_. The PRISMA method for determining inclusion and exclusion criteria. # Results Eleven articles were included, six randomized control trials and five retrospective cohort studies. Various balance interventions, visual interventions utilizing vestibulo-ocular reflex (VOR), and cervical manual therapy were used during VRT for athletes' post-concussion. Incorporating visual interventions and cervical manual therapy into early rehabilitation significantly reduced symptoms and time to return to sport. However, balance interventions did not have a significant effect on reducing time to return to sport when used as a sole intervention. # Conclusion Addressing VRT deficits in the acute stages of a concussion may contribute to a quicker resolution of symptoms and a quicker return to sport. More research needs to be performed to determine the effectiveness of early intervention of VRT in concussion recovery. # Level of Evidence 1